Relationship Between Eating Patterns And Sleep Patterns With The Incidence Of Obesity In School-Age Children At Petra Christian Elementary School, Kediri - Nani, Andrian; Yenny Puspitasari; Aprin Rusmawati (Universitas STRADA Indonesia, 2016)
Obesity is a condition o mass body indeks ( BMI ) of the gender. Obesity on children hood could make a deaseslike diabetic type 2. Beside that, could take a risk for being obesity in adult and it has couse metabolic glucose effects and degeneratif deaseas like heart deaseas and vesicular obstructions. The desingn of the research was observational with quantitative cross sectional approached. Respondents was taking with purpose sampilng technique. The population in this research were all sudents in Kristen Petra primary school are 466 respondents. Independent variable in this research was feed pattern and sleep partern and dependent variable was obesity incident. The rusult being analyzed by ordinal regression test wit α=0,05. The result of this research showed most of respondent has feed pattern good category that 22 respondents (61,2%), some respondent has sleep patter in enough category that 25 respondents (69,4%). Most of respondent with obesity incident get included in normally category that 22 respondents (61,1%). The analyse results showed that 0,000<α=0,05 then ho was a relationship beetween feed and sleep patterns to obesity incidents of childrenin Kristen Petra Primary school Kediri. Based on the results above, the conclussion of this research is there is relationship of feed and sheep pattern to obesity incident. It is because imegular feed pattern and sleep pattern of children could give bad effect for their grown time